IDENTIFICATION AND ANTIOXIDANT ACTIVITY TEST OF SOME COMPOUNDS FROM METHANOL EXTRACT PEEL OF BANANA (Musa paradisiaca Linn.) - Sri Atun; Retno Arianingrum; Sri Handayani; Rudyansah Rudyansah; Mary Garson (Universitas Gadjah Mada, 2007)
The objective of these research was measured activity as antioxidant some compounds in methanol extracts of peel of banana (Musa paradisiaca Linn.), isolated some compounds which had activities as antioxidant, and determined this structure. Method of this study was extracted powdered peel of banana with methanol at room temperature. Extract was concentrated in vaccuo and then successively was partitioned with n-hexane, chloroform, etyl acetate, and buthanol. Antioxidant test from each fractions was measured by hydroxyl radical scavenger test with Fenton reaction method. The result of this study showed activity each fractions as hydroxyl radical scavenger activity of chloroform, etyl acetate, and buthanol fraction were IC50 693.15; 2347.40; and 1071.14 mg/mL respectively. The isolation of secondary metabolite compounds from chloroform fraction obtained two isolate compounds. Identification by spectroscopy IR, MS, 1H and 13C NMR one and two dimension showed that the compounds are 5,6,7,4'-tetrahidroxy-3,4-flavan-diol and a new compound cyclohexenon derivative (2-cyclohexene-1-on-2,4,4-trimethyl-3-O-2'-hydroxypropyl ether).